FAKTOR PENENTU RETURN SAHAM DENGAN PRICE TO BOOK VALUE SEBAGAI VARIABEL MODERASI DI BURSA EFEK INDONESIA - Sri Lestari Kurniawati; Linda Purnama Sari; Nurul Hasanah Uswati Dewi (Jurnal Keuangan dan Perbankan, 2012)
The purpose of this study was to exemine the effect of the companys financial performance variables consistingof earning growth ratio, dividend payout ratio and size, the variable return equity price to book value as amoderating variable. The samples in this study were all companies listed on the Indonesia Stock Exchangefrom 2005 to 2010 by using purposive sampling with criteria that the company had a positive book value ofequity during the study period. The company splitted the cash dividend and the company did not do corporateactions such as stock splits, reverse stock, stock dividend. The data used in this study were all companies listedon the Indonesia Stock Exchange from 2005 to 2010 (except for companies engaged in finance and banking) byusing multiple linear regression to test the interaction or Multiple Regresion Analysis (MRA). The studyfound that the price to book value was not able to significantly moderate the effect of earning growth ratio,dividend payout ratio and size toward the stock return variable for the interaction test results showed thesignificant value was greater than interaction of alpha as 5%.